Beyond the Coffee Cup: Dynamics of Social Space Production in the Jalan Roda Culinary Tourism Area Manado City - Sangputri Sidik; Awaluddin Hasrin; Lalu Murdi; Nining Winarsih; Lukman Hakim (Universitas Hamzanwadi, 2024)
People's lives have changed in large cities due to the growth of coffee shops. Coffee consumption behavior has become a trend in contemporary society. This research aims to analyze the dynamics of space production in coffee shops in Jalan Roda Culinary Tourism Area (Jarod), Manado City, Indonesia. Researchers used a qualitative approach to describe the social reality in the Jalan Roda culinary tourism area of Manado City. In depth we interviewed visitors, shop owners, and related parties in the Jalan Roda culinary tourism area of Manado City. Observations were made to obtain a clearer picture of the situation and social practices in the Jalan Roda culinary tourism area of Manado City. This research shows that coffee shops are not only a static space but also a social stage that plays an important role in the social dynamics of contemporary society. Coffee consumption activities are not only limited to coffee drinks but also involve various social practices that contribute to the production of social space in certain areas. Coffee shops are a symbol of public space that can be accessed by all levels of society and a place for social and cultural interactions that are part of city life. This research contributes to developing the discourse of social space production and shows how social practices can shape and produce space in society.